Recurrent bacterial pneumonia due to immunoglobulin G2 subclass deficiency after allogeneic hematopoietic stem cell transplantation: Efficacy of immunoglobulin replacement. Issue 3 (25th March 2018) - Yamazaki, Rie; Kikuchi, Taku; Kato, Jun; Sakurai, Masatoshi; Koda, Yuya; Hashida, Risa; Yamane, Yusuke; Abe, Ryohei; Hasegawa, Naoki; Okamoto, Shinichiro; Mori, Takehiko
Abstract: Immunoglobulin (Ig) G2 subclass deficiency is known to be associated with recurrent bacterial respiratory infections caused by capsulated bacteria. We encountered a case of recurrent pneumonia due to Streptococcus pneumoniae after allogeneic hematopoietic stem cell transplantation (HSCT). IgG2 subclass level was specifically low, and prophylactic Ig replacement successfully prevented subsequent infections. However, the cessation of Ig replacement resulted in subsequent pneumonia. These findings suggested that IgG2 deficiency could be a cause of recurrent pneumococcal infection after allogeneic HSCT.